Implementing rapid e-learning through interactive materials development - Santally, Mohammad; Rajabalee, Yousra Banoor; Rajputh, Ravi (IGI Global, 2023)
"This research book presents relevant theoretical foundations for the design and development of interactive learning materials using the rapid e-learning method, drawing on research, case studies and/or reports from different contextual applications of the method, the challenges, and learning experiences of students"--
"Premier Reference Source" - cover page
Keywords: Web-based instruction; Teaching / Aids and devices / Design and construction; Educational technology; Curriculum planning